2021
DOI: 10.3390/nu13030880
|View full text |Cite
|
Sign up to set email alerts
|

Fast Eating Is Associated with Increased BMI among High-School Students

Abstract: Fast self-reported eating rate (SRER) has been associated with increased adiposity in children and adults. No studies have been conducted among high-school students, and SRER has not been validated vs. objective eating rate (OBER) in such populations. The objectives were to investigate (among high-school student populations) the association between OBER and BMI z-scores (BMIz), the validity of SRER vs. OBER, and potential differences in BMIz between SRER categories. Three studies were conducted. Study 1 includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
5
15
0
Order By: Relevance
“…Similar to previous studies [ 48 , 49 , 50 , 51 ], this study showed that eating quickly was associated with significantly higher rates of obesity in both adults and older adults than the overall rate. Recent studies have shown that eating quickly was associated with obesity from schoolchildren [ 48 ] and high school students [ 49 ] to the older adults [ 50 ], and it was associated not only with obesity but also with lower physical fitness [ 51 ]. Based on these results, care should be taken to prevent obesity in community-dwelling older adults who eat quickly, as well as to prevent low nutrition in those who eat slowly.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies [ 48 , 49 , 50 , 51 ], this study showed that eating quickly was associated with significantly higher rates of obesity in both adults and older adults than the overall rate. Recent studies have shown that eating quickly was associated with obesity from schoolchildren [ 48 ] and high school students [ 49 ] to the older adults [ 50 ], and it was associated not only with obesity but also with lower physical fitness [ 51 ]. Based on these results, care should be taken to prevent obesity in community-dwelling older adults who eat quickly, as well as to prevent low nutrition in those who eat slowly.…”
Section: Discussionsupporting
confidence: 90%
“…It is possible to find the average speed of the model proposed by Zandian et al [ 25 ] using Equation (9): the results are as follows: (a) the average eating speed of girls is 27.16 g/min; (b) boys—32.7 g/min, which are comparable with the values mentioned by Fagerberg et al [ 23 ].…”
Section: Methodssupporting
confidence: 71%
“…However, Fagerberg et al [ 23 ] applied a more simple model for food intake speed calculation—constant average speed (see Equation (6)): where E —food mass intake during time t .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations